The Saudi Red Crescent's Experience In Dealing With Severe Heat Waves A Field Case Study (The Review of Diabetic Studies, 2025)
This study examines the Saudi Red Crescent's experience in confronting extreme heat waves, one of the most significant climate challenges that directly impact the health of individuals and the safety of pilgrims and residents alike. The research relied on the descriptive analytical approach, where a questionnaire consisting of (15) items was designed and distributed to a field sample of (200) participants with the aim of identifying the level of readiness and response of the Red Crescent teams in such harsh conditions. The results of the study showed that the research tool has a high degree of stability and validity, as Cronbach's alpha coefficient reached (0.91), which indicates high reliability in measuring the targeted variables. The statistical results also showed that the overall average of responses was (4.20) with a standard deviation of (0.78), which reflects a high level of efficiency and readiness of the Red Crescent in dealing with injuries associated with heat waves. According to the descriptive analysis, the most prominent strengths were the regular training of field teams, rapid response to critical situations, and the provision of ambulances equipped to handle injuries resulting from sunstroke and heat stress. The results of the t-test for two independent samples also showed that there were statistically significant differences between the experimental and control groups in favor of the experimental group, as the value of (t = 2.10) reached a significance level of (0.037). The study concludes that the Saudi Red Crescent's experience represents an effective model for managing health crises resulting from climate change. It highlights the importance of investing in ongoing training, providing logistical support, enhancing awareness campaigns, and coordinating between various agencies to ensure a rapid and effective response that reduces injury and death rates during severe heat waves.